2023
DOI: 10.3390/jcm12227091
|View full text |Cite
|
Sign up to set email alerts
|

Application of Virtual Reality-Assisted Exergaming on the Rehabilitation of Children with Cerebral Palsy: A Systematic Review and Meta-Analysis

Muhammad Abubaker Tobaiqi,
Emad Ali Albadawi,
Hammad Ali Fadlalmola
et al.

Abstract: Background: Rehabilitation programs for children with cerebral palsy (CP) aim to improve their motor and cognitive skills through repeated and progressively challenging exercises. However, these exercises can be tedious and demotivating, which can affect the effectiveness and feasibility of the programs. To overcome this problem, virtual reality VR-assisted exergaming has emerged as a novel modality of physiotherapy that combines fun and motivation with physical activity. VR exergaming allows children with CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…The NIH Quality Assessment Tool of Controlled Intervention Studies was used for prospective randomized studies. These tools were used by two authors independently (CP and DL) [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The NIH Quality Assessment Tool of Controlled Intervention Studies was used for prospective randomized studies. These tools were used by two authors independently (CP and DL) [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Training or interventions aimed to enhance skills, including both motor [77][78][79][80][81][82][83][84] and cognitive skills [84][85][86], are proposed for disabled young people.…”
Section: Skillmentioning
confidence: 99%
“…Michelle et al's focus group interviews [77] identified training needs for supporting students with visual impairments, aiming to improve the motor skills of students with visual impairments. Virtual reality (VR)-assisted exergaming therapy [84] significantly improved outcomes for children with cerebral palsy, enhancing various motor and cognitive dimensions [84]. Aslan et al's study [81] highlighted the effectiveness of computer-aided video modeling in teaching basic basketball movements to individuals with Down syndrome, leading to an increased self-confidence and strengthened peer relations through active participation.…”
Section: Skillmentioning
confidence: 99%
“…(Verheijden Klomstra, Jaarsma, & Strömberg, 2014;Ingadottir et al, 2020;Jaarsma et al, 2021;Berglund et al, 2022). This method has shown promising results in healthy populations and might be considered as a progressive interventional setting in chronic disease populations (Street, Lacey, & Langdon, 2017;Stojan & Voelcker-Rehage, 2019;Cieślik et al, 2023;Moller et al, 2023;Tobaiqi et al, 2023). Efforts at organisational advances could perhaps focus on modifications in the existing IDE interventional setting, particularly in the creation of patients' self-care competences.…”
Section: Implications For Future Researchmentioning
confidence: 99%